Regulating the metabolic flux of pyruvate dehydrogenase bypass to enhance lipid production in Saccharomyces cerevisiae - Cairong Lei; Xiaopeng Guo; Miaomiao Zhang; Xiang Zhou; Nan Ding; Junle Ren; Meihan Liu; Chenglin Jia; Yajuan Wang; Jingru Zhao; Ziyi Dong; Dong Lu (Communications Biology)
Abstract To achieve high efficiency in microbial cell factories, it is crucial to redesign central carbon fluxes to ensure an adequate supply of precursors for producing high-value compounds. In this study, we employed a multi-omics approach to rearrange the central carbon flux of the pyruvate dehydrogenase (PDH) bypass, thereby enhancing the supply of intermediate precursors, specifically acetyl-CoA. This enhancement aimed to improve the biosynthesis of acetyl-CoA-derived compounds, such as terpenoids and fatty acid-derived molecules, in Saccharomyces cerevisiae. Through transcriptomic and lipidomic analyses, we identified ALD4 as a key regulatory gene influencing lipid metabolism. Genetic validation demonstrated that overexpression of the mitochondrial acetaldehyde dehydrogenase (ALDH) gene ALD4 resulted in a 20.1% increase in lipid production. This study provides theoretical support for optimising the performance of S. cerevisiae as a “cell factory” for the production of commercial compounds.